COMPARISON OF PLATELET RICH THERAPY ALONE WITH PLATELET RICH THERAPY ALONG WITH DAILY TOPICAL 5% PROCAPIL APPLICATION FOR THE TREATMENT OF ANDROGENETIC ALOPECIA: A QUASI-EXPERIMENTAL CLINICAL TRIAL - Khoso, Hina; Muhammad Fahim, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Androgenetic alopecia (AGA) affects up to 50% of males and 40% of females by the age of 50. It is the result of progressive, patterned hair loss that occurs in genetically predisposed individuals having hypersensitive androgen receptors in hair follicles. Due to the variable efficacy and adverse effect profile of FDA-approved drugs, newer and alternative modalities need to be utilized. As no prior study evaluated the efficacy of Procapil in combination with platelet-rich plasma (PRP), this study aimed to fill the research gap. The objectives were to assess the effectiveness of topical Procapil 5% combined with PRP vs PRP alone in androgenetic alopecia. It was a clinical trial conducted at the Tehsil Headquarters Hospital Takhtbhai Mardan. Methods: One hundred and sixty patients with AGA were selected and divided into two groups,80 in each. Group A received 4 sessions of PRP alone, 4 weeks apart while Group B was treated with PRP in combination with topical 5%procapil solution applied twice a day. Final results are calculated at the end of 6 months using 7- 7-point patient' satisfaction and dermatologist evaluation scoring systems. Results: The mean age in Groups A and B was 29.34±5.3 &30.22±4.8 respectively. Disease duration was comparable between both groups. At the final Assessment Greater proportion of patients in group B achieved better scores on Dermatologist evaluation and Patient satisfaction scales (p-value<0.05). Conclusion: It has been established that combining PRP with 5% Procapil yields better results in treating AGA compared to PRP used alone.